2021
DOI: 10.3390/children8040266
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between COVID-19 and Innate Immunity in Children: A Review

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the virus responsible for the pandemic viral pneumonia that was first identified in Wuhan, China, in December 2019, and has since rapidly spread around the world. The number of COVID-19 cases recorded in pediatric age is around 1% of the total. The immunological mechanisms that lead to a lower susceptibility or severity of pediatric patients are not entirely clear. At the same time, the immune dysregulation found in those children who developed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 64 publications
3
16
0
4
Order By: Relevance
“…Our findings consistently demonstrate that most respiratory morbidities decreased substantially during this first year of the pandemic. Thus, our data might be interpreted as support for the recent preliminary proposed explanation that the COVID‐19 virus and its consequences may play a role in the regulation of the immune system and affect the habitat for other respiratory viruses 33,34 . The relatively “sterile” conditions generated during lockdowns and restrictions, might impair the normal process of innate immune memory system training, 34–38 leaving the children in a more vulnerable state.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Our findings consistently demonstrate that most respiratory morbidities decreased substantially during this first year of the pandemic. Thus, our data might be interpreted as support for the recent preliminary proposed explanation that the COVID‐19 virus and its consequences may play a role in the regulation of the immune system and affect the habitat for other respiratory viruses 33,34 . The relatively “sterile” conditions generated during lockdowns and restrictions, might impair the normal process of innate immune memory system training, 34–38 leaving the children in a more vulnerable state.…”
Section: Discussionsupporting
confidence: 76%
“…Thus, our data might be interpreted as support for the recent preliminary proposed explanation that the COVID-19 virus and its consequences may play a role in the regulation of the immune system and affect the habitat for other respiratory viruses. 33,34 The relatively "sterile" conditions generated during lockdowns and restrictions, might impair the normal process of innate immune memory system training, [34][35][36][37][38] leaving the children in a more vulnerable state. This might contribute to the subsequent unexpected rise in morbidities.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, future research should concentrate on the absolute degree of defense provided by trained immunity. 168 Large randomized BCG vaccination trials are required to substantiate the protective effects of BCG vaccination against COVID-19. 169 It is also necessary to investigate the molecular pathways that inhibit the innate immune cells from reprogramming to a suppressive phenotype in extreme COVID-19 cases.…”
Section: Therapeutic Targeting Of Trained Immunitymentioning
confidence: 99%
“…Both vaccines consist of modified RNA that encodes a version of the SARS-CoV-2 spike protein containing mutations that lock the protein into a conformation that can induce neutralizing antibody responses. Studies have shown that they induce both humoral and cellular immunity [ 29 , 30 ]. Many other vaccines are still under clinical trials.…”
Section: Vaccination As Prophylaxismentioning
confidence: 99%